2017
DOI: 10.12688/f1000research.11255.2
|View full text |Cite
|
Sign up to set email alerts
|

Wash-in and wash-out of sevoflurane in a test-lung model: A comparison between Aisys and FLOW-i

Abstract: Background: Modern anaesthesia workstations are reassuringly tight and are equipped with effective gas monitoring, thus providing good opportunities for low/minimal flow anaesthesia. A prerequisite for effective low flow anaesthesia is the possibility to rapidly increase and decrease gas concentrations in the circle system, thereby controlling the depth of anaesthesia.  Methods: We studied the wash-in and wash-out of sevoflurane in the circle system with fixed fresh gas flow and vaporizer setting. We compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Data showed that the time to reach the target concentration did not depend on the FGF in the circle breathing system. At first instance, this observation seems unusual because flow-dependent wash-in times have been described for different anaesthetic machines by prior researchers and this further corresponds to the perception of anaesthetists in clinical practice [5,6]. However, it is known that the Aisys CS™ anaesthesia ventilator with the VA-specific Aladin™ cassette controls the VA output independent of the manually adjusted FGF.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Data showed that the time to reach the target concentration did not depend on the FGF in the circle breathing system. At first instance, this observation seems unusual because flow-dependent wash-in times have been described for different anaesthetic machines by prior researchers and this further corresponds to the perception of anaesthetists in clinical practice [5,6]. However, it is known that the Aisys CS™ anaesthesia ventilator with the VA-specific Aladin™ cassette controls the VA output independent of the manually adjusted FGF.…”
Section: Discussionmentioning
confidence: 80%
“…An anaesthesia gas scavenging system is connected (5). The circle breathing system is connected via a heat moisture exchanger (6) to the test lung box with two bag-valve units (BV) with a volume of 2 l each. b ACD.…”
Section: Experimental Settingmentioning
confidence: 99%
“…and a F V S of 8%. They found that the F A S reached 1 MAC (2.1%) at 547 ± 83 and 38 ± 6 sec, respectively [5]. Leijonhufvud [12].…”
Section: Jakobsson Et Al Reported a Wash-in In A Test-lung Model Witmentioning
confidence: 98%
“…Thus, the target of F A S during anesthesia in daily practice varies between 1 to 3.5%, depending on the adjuvant drugs used. A good wash-in scheme should be able to precisely and promptly achieve every target of F A S. There are a few reports regarding wash-in schemes of sevoflurane LFA but those studies achieved only one or two targets of F A S [3][4][5]. In highly developed healthcare areas-where an anesthetic gas monitor is placed in every operating theatre-a wash-in scheme would be unnecessary.…”
Section: Introductionmentioning
confidence: 99%